Effect of cooking styles on the lipid oxidation and fatty acid composition of grass carp (ctenopharynyodon idellus) fillet - Zhang, J.; Wu, D.; Liu, D.; Fang, Zhongxiang; Chen, J.; Hu, Y.; Ye, X. (Cancer Council of Australia, 2013)
The effects of six cooking styles, including boiling, steaming, microwaving, grilling, pan-frying and deep-frying, on the lipid oxidation and fatty acid composition of grass carp (Ctenopharyngodon idellus) fillets were investigated. All treatments reduced the moisture contents and increased the relative ratio of protein. Compared with raw samples, the proportions of polar lipid fractions of all samples were increased, while free amino acid contents were significantly decreased. Peroxide values decreased during pan-frying and deep-frying, but remained constant in the samples subjected to the other four cooking methods. Microwave baking and grilling increased the p-anisidine values and resulted in higher lipid oxidative extents. Boiling, steaming, microwave baking and grilling did not affect the fatty acid composition. Pan-frying and deep-frying increased the general polyunsaturated fatty acid content and decreased the n–3/n–6 ratio, especially for the deep-frying cooking method. Fish consumption has been linked to health benefits such as reduced risk of coronary heart disease. This is largely attributed to the lipid, cholesterol, fatty acid composition and the polyunsaturated fatty acids present in fish oils. The ω–3 : ω–6 and polyunsaturated fatty acid/saturated fatty acid ratios are considered to be useful criteria for comparing relative nutritional and oxidation values of fish oils. This study was therefore conducted to determine the influence of different cooking styles on the lipid oxidation of grass carp. These features and information are very important to the food health industry because they could be potential guidelines for the clinical, community, foodservice and research dieticians to recommend the proper cooking methods to get better health effects. It is also useful for academic studies on food composition and nutrition.